2013
DOI: 10.1590/s1415-52732013000100002
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento infantil comparado com as referências NCHS e o padrão WHO/2006

Abstract: Este trabalho teve como objetivo analisar o crescimento de crianças em regime de aleitamento materno exclusivo até o sexto mês, bem como comparar seu peso e comprimento com a referência do National Center for Health Statistics 1978 e com o padrão da World Health Organization 2006. MétodosTrata-se de estudo longitudinal realizado em um Banco de Leite Humano, na cidade de São Luís, Maranhão, entre outubro de 2007 e novembro de 2008. Foi feita amostragem não probabilística com 328 crianças nascidas a termo e subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
1
7
0
3
Order By: Relevance
“…Boys tend to have a higher birth weight and a faster weight gain rate 8 . A discussion is presented by Jaldin et al 4 , which is based on other studies and justifies this difference between genders by anatomical and physiological characteristics, where boys have larger body structures and muscle tissue and girls have lower birth weight. In view of the above, one would expect that higher growth rates be observed among boys.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Boys tend to have a higher birth weight and a faster weight gain rate 8 . A discussion is presented by Jaldin et al 4 , which is based on other studies and justifies this difference between genders by anatomical and physiological characteristics, where boys have larger body structures and muscle tissue and girls have lower birth weight. In view of the above, one would expect that higher growth rates be observed among boys.…”
Section: Discussionmentioning
confidence: 91%
“…In the study by Spyrides et al 8 with children up to nine months of age, lower weight and size gain rates were also observed among girls. A study 4 that analyzed data from 181 children on exclusive breastfeeding (EBF) up to the sixth month of age found that boys' weight gain was higher only in the first quarter. The study by Mihrshahi et al 17 observed that male gender was a non-modifiable factor for rapid weight gain among children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Due to these major impacts, a public awareness about the benefits of breastfeeding (AM) and the training for the health professionals on this topic have been increasingly valued in the public and private health system, 4 reflecting on since 1991, when the World Health Organization (WHO), in association with the United Nations Children's Fund (UNICEF), to establish its goal in order to promote, protect and support breastfeeding worldwidely. 5 The medical literature contains strong evidence about the benefits of breastfeeding, 6 such as optimizing children's growth and physical and mental development and extensive protection against the main diseases that occur later in life. Recent data indicate that breastfeeding is an effective food strategy to prevent necrotizing enterocolitis in the premature population, 7 also presenting advantages for women's health, as for the increase of postpartum infertility period, a greater facility in the pregestational weight acquisition and risk reduction of developing breast and ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%